Advanced glycation end products and chronic inflammation in adult survivors of childhood leukemia treated with hematopoietic stem cell transplantation. Issue 3 (9th December 2019) - Felicetti, Francesco; Cento, Alessia Sofia; Fornengo, Paolo; Cassader, Maurizio; Mastrocola, Raffaella; D'Ascenzo, Fabrizio; Settanni, Fabio; Benso, Andrea; Arvat, Emanuela; Collino, Massimo; Fagioli, Franca; Aragno, Manuela; et al.
Abstract: Background: Among survivors of pediatric acute lymphoblastic leukemia (ALL), those who received hematopoietic stem cell transplantation (HSCT) conditioned with total‐body irradiation (TBI) show the highest risk of late complications, including cardiovascular (CV) disease. Advanced glycation end products (AGEs) have been associated with CV disease in diabetes mellitus and other clinical conditions. This study explores AGEs plasma levels, inflammatory status, and lipid profile in survivors of pediatric ALL who received HSCT conditioned with TBI. Procedure: Inclusion criteria were (a) previous diagnosis of ALL at age < 18 years, treated with HSCT conditioned with TBI; (b) age > 18 at the time of the study enrollment; (c) off‐therapy for at least five years. Radiotherapy other than TBI, preexisting heart disease, glucose metabolism impairment, body mass index > 25, active graft versus host disease (GvHD), smoking, or treatment with cholesterol lowering medications were exclusion criteria. Eighteen survivors and 30 age‐matched healthy controls were enrolled. Results: AGEs plasma levels were markedly higher in ALL survivors than in healthy subjects (2.15 ± 2.21 vs 0.29 ± 0.15 pg/mL, P < 0.01). Survivors also showed higher levels of high‐sensitivity C‐reactive protein (2.32 ± 1.70 vs 0.88 ± 1.09 mg/dL, P < 0.05), IL‐1β (7.04 ± 1.52 vs 4.64 ± 2.02 pg/mL, P < 0.001), IL17 (37.44 ± 3.51 vs 25.19 ± 6.34 pg/mL, P < 0.001), an increased glutathione/reduced glutathione ratio (0.085 ± 0.07 vs 0.041 ± 0.036, P < 0.05) and slight alterations in their lipid profile. Conclusions: Our data show AGEs accumulation and chronic inflammation in ALL survivors who received HSCT conditioned with TBI. These alterations may contribute to the increased risk of CV disease reported in these subjects.